RANCANG BANGUN PROTOKOL KEAMANAN SMS BANKING - , I Made Sunia Raharja ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Rapidly growing use of the smartphone has lead to the large amount of mobile service utilization by the society. SMS Banking is one of the frequently used service. However, security issue is often ignored by the provider of SMS Banking services. The standard SMS technology usually applied in common SMS Banking service is wellknown to be very vulnerable to tapping. Therefore, an SMS Banking protocol, providing information security service in transactional message is urgently in need. Information security can be achieved through several security mechanism i.e. enchipherment, digital signature, data integrity and key exchange. These mechanisms are applicable through implementation of cryptography. There are two type of cryptography, symmetric cryptography and asymmetric cryptography. SMS Banking security protocol in this research runs through two step. The first step is transmission of transaction request and the second step is transaction process. Encipherment is conducted using 3DES symmetric cryptography. Digital signature and data integrity are conducted using ECDSA asymmetric cryptography. Mean while, the key exchange is conducted using ECDH. Test result showed that the implementation of the protocol can conduct SMS Banking service and provide protection over costumerâs PIN. In general, this protocol have fulfill the X.800 security services.